Turkish waqf after the 2004 Aceh tsunami - Tekin, Alaeddin; Islam, Arshad (IIUM Press, International Islamic University Malaysia, 2018)
This paper studies waqf projects including schools, mosques,orphanages and housing built by Turkish aid agencies in Aceh province of Indonesia after the 2004 Aceh Tsunami following the Indian Ocean Earthquake. Such projects continue to be actively supported and to serve the Acehnese community, playing an important role with local organizations. Besides the Turkish Government, NGOs such as Turkish Foundation Institutions including the Turkish Red Crescent (Kızılay), Deniz Feneri and Humanitarian Relief Foundation (IHH) are the main groups considered in this study. The paper situates Turkish waqf in the long-term history of relations between Turkey and Aceh, dating from the mid-16th century, which was reinvigorated by Turkish solidarity following the 2004 tsunami. Essentially, the fact that there is a serious lack of literature on studies of these institutions and activities and their deeper cultural signifcance is the main rationale for presenting this work. The main purpose of this study is to examine the foundation and relief works from Turkey to Aceh after the shocking earthquake of 9.1 magnitude, which resulted in 126,741 deaths, 93,285 missing and massive destruction of property and infrastructure on 26th December 2004 in Aceh.